2018
DOI: 10.1093/eurpub/cky050
|View full text |Cite
|
Sign up to set email alerts
|

The association between diabetes and depressive symptoms varies by quality of diabetes care across Europe

Abstract: BackgroundDepressive symptoms are more common in adults with diabetes and may arise from the physical and psychosocial burden of disease. Better quality of diabetes care may be associated with a reduced disease burden and fewer depressive symptoms.MethodsThis cross-sectional study included 34 420 participants from 19 countries in the European Social Survey Round 7 (2014–2015). Countries were grouped into quartiles based on their quality of diabetes care as measured in the Euro Diabetes Index 2014. Individual-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Effective diabetes management and depressive symptoms appear inter‐connected. In a large study including over 30 000 participants from 19 European countries, the association between diabetes and depressive symptoms appears stronger in countries with lower quality of diabetes care . Associations between knowledge of diabetes diagnosis and depressive symptoms and health‐related quality of life are moderated by sociodemographic factors and social support and depressive symptoms among people with Type 2 diabetes may be attributed to health‐related quality of life, rather than to glucose metabolism .…”
Section: Discussionmentioning
confidence: 99%
“…Effective diabetes management and depressive symptoms appear inter‐connected. In a large study including over 30 000 participants from 19 European countries, the association between diabetes and depressive symptoms appears stronger in countries with lower quality of diabetes care . Associations between knowledge of diabetes diagnosis and depressive symptoms and health‐related quality of life are moderated by sociodemographic factors and social support and depressive symptoms among people with Type 2 diabetes may be attributed to health‐related quality of life, rather than to glucose metabolism .…”
Section: Discussionmentioning
confidence: 99%
“…This was surprising, given the overall quality of diabetes care in England compared with other countries. 16 33 34 Possible population and healthcare professional factors should be examined to better understand the increased odds of undiagnosed depression among people with diabetes in England. Results from the USA were consistent with the limited available evidence that diabetes is associated with increased access to depression diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…15 Specifically, in countries scoring in the highest quartile, having diabetes was associated with a 3% relative increase in depressive symptoms (95% CI 1.00 to 1.05) compared with a 22% (1.14–1.31) relative increase in countries scoring within the lowest quartile of diabetes care quality. 16 The authors suggested related pathways for this association may include financial aspects of diabetes care, access to services and differential exposure to social determinants of health. These findings suggest that improved quality of diabetes care may reduce some of the psychological burden associated with living with diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression among women workers may be associated to burden of having diabetes while maintaining a career which might affects their daily life. Likewise, responsibility to family and children may afflict women in managing diabetes (Aliaga, 2006;Graham, Thomson & Bambra, 2018).…”
Section: Motivationmentioning
confidence: 99%